(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English Fish and fish-based products are main protein sources for Indonesian. Their production and availability are so varied by provinces and major islands. Consequently, their average consumption levels are spatially different. The inequality of consumption and production is traced to the problems of marketing and distribution. By understanding and solving the problems, per capita fish consumption level may be increased. The existing marketing organizations at producer level do not provide incentives to boost the production. Meanwhile, the marketing facilities and infrastructures are limited available. For the future development, particularly for increasing per capita fish consumption, supporting marketing facilities and infrastructures should be provided by the government. Other functions of the government are to provide regulations on the management of local fish auction markets, to undertake campaign of fish consumption, to provide marketing information in order to attract private sectors into the business, and to carry out research and development in order to anticipate changes of consumption pattern. ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Indonesian Ikan merupakan sumber protein utama bagi penduduk. Namun distribusi produksinya sangat timpang menurut wilayah. Akibatnya konsumsi ikan tidak merata.Ketidakseimbangan antara produksi dan konsumsi merupakan masalah pemasaran dan distribusi. Dengan memahami kondisi pemasaran, distribusi, serta faktor-faktor yang mempengaruhi tingkat konsumsi maka di harapkan konsumsi ikan yang rendah dapat ditingkatkan. Organisasi pemasaran yang ada di tingkat nelayan belum sepenuhnya memberikan insentif bagi pengembangan produksi. Sarana dan prasarana pemasaran masih sangat terbatas. Ke depan, pemerintah sebaiknya mengambil bagian dalam penyediaan sarana yang cukup, penataan pemasaran di tingkat produsen melalui peraturan yang mempertimbangka kondisi lokal, pengadaa kampanye guna meningkatkan konsumsi, pemberian kesempatan bagi swasta untuk berpartisipasi secara luas melalui penyediaan informasi pasar, serta mengadakan penelitian untuk mengantisipasi dan menyikapi perubahan konsumsi yang diakibatkan oleh perubahan lingkungan di masa yang akan datang.